Hungarian Regulation of Subjects Excluded from the Referendum - Sasvári, Róbert (Közigazgatási és Infokommunikációs Jogi PhD Tanulmányok, 2021)
The paper aims to explore the issues of the excluded and forbidden subjects of the referendum under the Hungarian rules, thus making it comparable with similar legislation in other jurisdictions. A consistent examination of these rules and jurisprudence will lead to an exploration of the requirements that a referendum initiative in Hungary must actually meet in order to pass the scrutiny of the body that controls the issues.